Stabilization of Sarawak peat by different types of stabilizer - Md. Aminur, Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The present research describes a study on tropical peat soil stabilization by using different chemicals to improve physical and geotechnical properties. The samples were collected from eight different locations of Matang, Sarawak, Malaysia. Among them, two samples were selected with higher percentage of organic content for geotechnical characterization and the remaining samples were used only for physical characterization. In this study, ordinary Portland cement (OPC), quick lime (QL), coal fly ash (FA) and different types of chemical namely, C 1 (Mix of 2% sodium sulphate (Na2S04), 0.50% sodium chloride (NaCl) and 0.10% triethanolamine (C6HJsN03»; C2 (2.60% Calcium sulphate (CaS04» and C3 (2.60% Aluminum sulphate (Ah(S04)3» and 2% NaOH were used with peat soil samples to check the strength gain The amount of OPC, QL and FA added to the peat soil sample, as percentage of the dry soil mass, were in the range of 5 to 25%; 2 to 8% and 5 to 25%, respectively. The Unconfined Compressive Strength (UCS) tests were carried out for curing period of 7 - 120 days and the California Bearing Ratio (CBR) tests were carried out after 96 hours of soaking on treated/untreated peat soil samples. The result shows that, UCS and CBR values increases significantly with the increase of stabilizers used. However, in case of FA and QL, the UCS value increases up to 20% & 6%, respectively with a curing period of 28 days but decreases or rather steady beyond this percentage. Comparing the performance ofthese stabilizers, ordinary Portland cement is the most suitable stabilizer, but in case of 5% OPC and FA plus 2.6% CaS04 where the peat soil was first treated with NaOH is better than only 5% OPC and FA stabilized peat soil. Few UCS tests have been conducted with the combination of FA and QL to study their combined effect. The CBR result for combination ofFA and ope shows better strength, as compared with only FA and peat soil. The present research also establish few correlations between different physical and geotechnical properties of tropical peat soils from Sarawak, Malaysia and the results indicate reasonably good correlations for this particular tropical peat soil. A design chart has also been developed on treated peat soil with different types of stabilizers. Engineers can refer to these correlations and design chart in order to comprehend the preliminary behavior and to determine the ultimate bearing capacity of stabilized peat soil for long term curing period, where the geotechnical data are not readily available. In addition, few Scanning Electron Microscope (SEM) studies were carried out on original and stabilized peat soil to investigate their microstructure.